2017
DOI: 10.1080/1343943x.2017.1283963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated CO2 concentration on growth and photosynthesis of Chinese yam under different temperature regimes

Abstract: Chinese yam ('yam')

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Tipping and Murray (1999), in researching Panicum trichanthum, P. antidotale, and P. decipiens, attributed increased starch accumulation at elevated [CO 2 ] to enhanced photosynthesis. In this study, our results suggested that the increased starch grain accumulation in the chloroplast under elevated [CO 2 ] may be caused by an increase in the leaf photosynthetic rate under elevated [CO 2 ] (Thinh et al, 2017a) and act as a mechanism for storing carbon.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Tipping and Murray (1999), in researching Panicum trichanthum, P. antidotale, and P. decipiens, attributed increased starch accumulation at elevated [CO 2 ] to enhanced photosynthesis. In this study, our results suggested that the increased starch grain accumulation in the chloroplast under elevated [CO 2 ] may be caused by an increase in the leaf photosynthetic rate under elevated [CO 2 ] (Thinh et al, 2017a) and act as a mechanism for storing carbon.…”
Section: Discussionmentioning
confidence: 64%
“…However, it is widely assumed that photorespiration is suppressed at high [CO 2 ]. In our previous study (Thinh et al, 2017a), we found that the net photosynthetic rate was 36-73% higher in Chinese yams grown under elevated [CO 2 ] than under ambient [CO 2 ]. These results suggest that an increase in the number of chloroplasts in Chinese yam leaves is one of the factors underlying the increase in photosynthesis under elevated [CO 2 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations